The Challenges Confronting Islamic Education in Guinea - Aboubacar Barry; Mariam Elbanna (Walidem Institute and Publishing (WIP), 2025)
Objective: This study aims to explore the challenges faced by Islamic education in Guinea, focusing on the influence of cultural, social, and economic factors on religious education. Theoretical Framework: An Islamic values- and principles-based approach is used to analyze how cultural, social, and economic factors affect religious awareness and the effectiveness of Islamic education in Guinea. Literature Review: An analysis of the literature related to globalization and its impact on religious education, a study on the lack of an integrated religious curriculum in the education system, and previous research on Islamic education in countries with similar situations. Methods: Using a descriptive-analytical approach, this study reviewed relevant literature and conducted interviews with teachers, parents, and students from various Islamic schools. Results: The results of the study show that the main challenges include the impact of globalization which weakens the commitment of youth to religious values, the lack of an integrated religious curriculum, the lack of religious awareness among the youth, and the limitation of effective educational programs in fostering a correct understanding of Islam. Implications: This study recommends the development of an integrated religious curriculum, adequate teacher training, and increased role of families and communities in supporting Islamic education. Novelty: This study makes a unique contribution by identifying the relationship between social, cultural, and economic factors to the challenges of Islamic education in Guinea, while also offering practical recommendations to improve the effectiveness of religious education in the local context.